Precise method of in situ drought stress induction in flax (Linum usitatissimum) for RNA isolation towards down-stream analysis - Gupta, Payal; Dash, Prasanta K. (Annals of Agricultural Research, 2015)
Hydropenia (drought stress) is a major abiotic stress to all plants at all stages. Its impact and elicitation of subsequent symptoms on plants varies depending upon the robustness of crop. Flax/linseed, economically a unique crop that yields both oil and fibre is vulnerable to drought. With release of flax genome sequence data, the molecular research has gained impetus to identify novel genes involved in biotic and abiotic stress in this crop. Since gene discovery in a new crop relies on precise induction of stress and correct stage of symptom elicitation, we report here a standardized in situ condition and successfully demonstrate the duration and symptoms that must be elicited for drought stress related molecular studies in flax. Our study involved with-holding of water for a duration of 10 days which elicited symptoms on fourth day that gradually lead to mortality of plants with concomitant decrease in total RNA accumulation.